Band of Robbers [videorecording (DVD)] - West, Joel P. (Fisher Klingenstein Ventures, 2016)
Follows grown-up versions of Mark Twain's characters Huck Finn and Tom Sawyer as they reconnect after Huck's prison release and Tom, a corrupt cop, forms the Band of Robbers--including friends Joe Harper and Ben Rogers--and together, they set off to find the hidden treasure of their childhood.